Seasonal Fish Assemblage Structure Using Environmental DNA in the Yangtze Estuary and Its Adjacent Waters - Zhang, Hui; Yoshizawa, Susumu; Iwasaki, Wataru; Xian, Weiwei (Frontiers in Marine Science, 2019)
The fisheries resources of the Yangtze Estuary and its adjacent waters have undergone dramatic declines as a consequence of environmental changes and human activities, with traditional ecological investigations demonstrating progressive decreases in species diversity and annual numbers in the fisheries resource. Environmental DNA (eDNA) technology has been demonstrated as an effective tool by many studies for detecting fish species, monitoring fish biodiversity and indicate the fish abundance. In the present study, we chose the Yangtze Estuary and its adjacent waters as a primary research area to investigate fish assemblage structure using eDNA technology. A total of 50 eDNA samples were collected in the estuary in 2018. The results showed that 41 operational taxonomic units were identified from three seasons, with 18, 12 and 33 fish species associated specifically with spring, summer and autumn, respectively. The fish assemblage differed significantly among seasons. Canonical correspondence analysis showed that water temperature, salinity, and dissolved oxygen were the main environmental factors affecting structure of the seasonal assemblages. Results of the present study indicate that eDNA technology can be an effective tool not only for fisheries monitoring, but might also importantly assist marine resources conservation, sustainable exploitation of fisheries, the aquatic products processing industry, eco-friendly development, and socioeconomic stability.